2019
DOI: 10.1101/753087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and phenotypic characterization ofBurkholderiaisolates from the potable water system of the International Space Station

Abstract: The opportunistic pathogens Burkholderia cepacia and Burkholderia contaminans, both genomovars of the Burkholderia cepacia complex (BCC), are frequently cultured from the potable water system (PWS) of the International Space Station (ISS). Here, we sequenced the genomes and conducted phenotypic assays to characterize these Burkholderia isolates. All recovered isolates of the two species fall within monophyletic clades based on phylogenomic trees of conserved single-copy core genes. Within species, the ISS PWS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…With a few exceptions, biofilm formation rates were generally consistent across each genomovar. Overall, O’Rourke et al (2020) concluded that while the populations of Burkholderia present in the ISS PWS each maintained virulence, they probably were not more virulent than those that might be encountered on Earth and were found to be susceptible to clinically used antibiotics [ 41 ].…”
Section: Biofilms In Spacecraftmentioning
confidence: 99%
“…With a few exceptions, biofilm formation rates were generally consistent across each genomovar. Overall, O’Rourke et al (2020) concluded that while the populations of Burkholderia present in the ISS PWS each maintained virulence, they probably were not more virulent than those that might be encountered on Earth and were found to be susceptible to clinically used antibiotics [ 41 ].…”
Section: Biofilms In Spacecraftmentioning
confidence: 99%